2019
DOI: 10.1016/j.apsb.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficient lung cancer-targeted drug delivery via a nanoparticle/MSC system

Abstract: Low targeting efficiency limits the applications of nanoparticles in cancer therapy. The fact that mesenchymal stem cells (MSC) trapped in the lung after systemic infusion is a disadvantage for cell therapy purposes. Here, we utilized MSC as lung cancer-targeted drug delivery vehicles by loading nanoparticles (NP) with anti-cancer drug. MSC showed a higher drug intake capacity than fibroblasts. In addition, MSC showed predominant lung trapping in both rabbit and monkey. IR-780 dye, a fluorescent probe used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 31 publications
2
59
0
Order By: Relevance
“…More so, lung-predominant circulation is the most significant characteristics of MSC employed as lung-targeted drug delivery system. This was buttressed by Wang and his colleagues [ 59 ] where the distribution of MSC was observed in lung of mice, rabbits and monkey following intravenous injection, whereas, all MSC transplanted are xenogenic. It was further reported that the MSC targeted drug delivery nanoparticulate system have a greater ability to inhibits primary tumours similar to that of NP loaded docetaxel drug system.…”
Section: Nanotechnology In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…More so, lung-predominant circulation is the most significant characteristics of MSC employed as lung-targeted drug delivery system. This was buttressed by Wang and his colleagues [ 59 ] where the distribution of MSC was observed in lung of mice, rabbits and monkey following intravenous injection, whereas, all MSC transplanted are xenogenic. It was further reported that the MSC targeted drug delivery nanoparticulate system have a greater ability to inhibits primary tumours similar to that of NP loaded docetaxel drug system.…”
Section: Nanotechnology In Cancer Treatmentmentioning
confidence: 99%
“…More so, the nano-system inhibits the tumour growth efficiently by blocking the signalling pathways of hypoxia cancer stem cells without causing any significant adverse effect during the period of the treatment. In another related study by Wang et al [ 59 ], the activity of mesenchymal stem cells (MSC) targeted drug delivery and NP loaded docetaxel as lung cancer treatment was investigated. Since it has been reported that MSC can be isolate from the bone marrow of patients and culture with ease, and transplant back into the patients for treatment so as to avoid immune rejection.…”
Section: Nanotechnology In Cancer Treatmentmentioning
confidence: 99%
“…Interestingly, these NP-loaded MSCs significantly inhibited tumor growth and enhanced survival of mice, though total doses of PTX-NPs were much lower than that of PTX solution or PTX-NPs alone [73]. It was found that MSCs were first entrapped in the lung parenchyma tissue and then migrated toward tumor sites due to their tumor-tropic effect [74,75]. The approach that increases the uptake of NPs by cells may improve therapeutic outcomes.…”
Section: Nanoparticles (Nps)-carrying Stem Cellsmentioning
confidence: 99%
“…Observation of its expression suggests a phagocytic function of GinPa-MSCs for incorporating drugs ( Brini et al, 2016 ). The high expression levels of endocytosis mediator clathrin in hAD-MSCs showed that drugs might internalize through receptor-mediated endocytosis ( Wang X. et al, 2019 ).…”
Section: Mscs In Drug Delivery Systemsmentioning
confidence: 99%